The EC bioethanol blend mandate policy: its effect on ACP sugar trade and potential interaction with EPA policies - Sukati, M.A. (2013)
The study aim was to determine effects of the EC bioethanol blend mandate policy and its potential interaction with the EPA policies on EU/ACP countries. The research analysis focussed on welfare outcomes, changes in trade balance and output of bioethanol crops commodities due to these policies. Emphasis of our analysis was placed on sugar given the economic importance of this commodity to many ACP member states. Absence of an EU bioethanol partial equilbrium model means we had to design one from certain assumptions. One of the assumptions was that subsidies support EU bioethanol production such that just enough is produced to meet the 5.75% and 10% EC blend mandate requirements. For this reason, EU bioethanol production did not affect transport fuel demand and prices. Using the GTAP model, the study has found that the EC bioethanol blend mandate policy increases bioethanol crops commodities prices resulting in global welfare loss that is highest in the EU region. However, the EC bioethanol blend mandate policy also increases bioethanol crops commodities production in ACP countries and promote ACP export of these commodities to the EU. The EU is able to produce all bioethanol requirements from local sugar beet production. Increasing the amount of sugar beet in bioethanol production minimizes the effect on global food prices and offers greatest benefits to ACP countries through promotion of their sugar industries. Trade liberalising EPA policies result in welfare gain for regions engaged in them. However, the EC bioethanol blend mandate policy’s interaction with the EPA policies result in welfare loss, which is again highest in the EU. Combination of the EC bioethanol blend mandate/EPA policies also promotes ACP bioethanol crops production and export. Overall, the study has contributed to our understanding of biofuel policies and their potential global effects on food markets especially in ACP countries.